ANALISIS RISIKO PAPARAN BENZENA TERHADAP KADAR FENOL DALAM URINE PADA PEKERJA HOME INDUSTRY REPARASI “BULU SHOES” SEMARANG - Raudatul Jannah; Siswi Jayanti; Ida Wahyuni; Daru Lestantyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
One of the toxic chemicals used in the shoe industry is benzene. Benzene itself is one of a variety of aromatic hydrocarbon compounds which are usually found in glue as an adhesive. Benzene is a chemical that has very high absorption power into the body, benzene that enters the body will experience the main metabolism to be benzene epoxide. In the liver, benzene epoxides undergo changes to form phenols that will be excreted in the urine, therefore phenol levels are used as biological indicators of benzene exposure. This study aims to describe the risk of exposure to benzene to Bulu Shoes Semarang home industry repair workers, but also to describe the source of benzene exposure, worker characteristics and analysis of phenol levels in urine. This research is a descriptive qualitative research with cross sectional approach. The number of informants in this study were 6 people. The results of the study revealed that the main source of benzene exposure was glue as an adhesive. Based on the results of laboratory measurements of urine phenol with NAB ≥ 25 mg / L, it is known that 2 people in the gluing section are known to have phenol levels in urine that exceeds the NAV of 25.61 mg / L and 2 other informants in the sewing section are close to the NAB, namely each - 24.78 mg / L and 20.61 mg / L respectively, for other informants namely in the depiction of the pattern and the cashier each had phenol levels in the urine of 3.67 mg / L and 15.75 mg / L. The conclusion in this study is that glue as the main source of exposure to benzene increases the risk of phenol levels in urine which is also influenced by individual characteristics, habits and types of work.